Radicalism and Fundamentalism in the Perspective of Contemporary Islamic Theology - Kusuma, Perdana; Pratama, Randi Surya; Surawan, Surawan (FiTUA: Jurnal Studi Islam, 2025)
Radicalism and fundamentalism in contemporary Islam have become pressing global issues that significantly affect social, political, and cultural dynamics. This study adopts a qualitative approach through library research to analyze the relationship between radicalism, fundamentalism, and contemporary Islamic theology as an alternative framework. The findings indicate that radicalism is often rooted in literal and partial religious interpretations, socio-political dissatisfaction, and cultural resistance to modernization. Fundamentalism, meanwhile, provides the ideological foundation for exclusivism and intolerance, which in turn can escalate into radical practices. In response, contemporary Islamic theology emphasizes rational, critical, and contextual approaches that prioritize dialogue, pluralism, inclusivity, and humanism. By reconstructing religious thought, reinterpreting sacred texts, and applying these perspectives in education and social institutions, contemporary theology serves as a strategic instrument to counter radical ideologies. This article argues that revitalizing contemporary Islamic theology is essential to fostering moderate, tolerant, and humanistic religious practices that remain relevant to modern challenges while upholding universal values of peace and justice.